Distribution of refractive errors and horizontal concomitant strabismus in Iraqi children - Hassan A. Aljaberi; Saeed Rahmani; Humam H. Alrikabi (PLoS ONE, 2026)
Horizontal concomitant strabismus is a common pediatric ocular disorder influenced by underlying refractive error patterns, yet evidence from Iraq remains limited. This study characterized refractive profiles in esotropia and exotropia and identified refractive predictors of each subtype. In this retrospective multicenter clinic-based case-comparison study, medical records of 2,256 children aged 4–15 years evaluated at three tertiary pediatric ophthalmology centers in Iraq were reviewed; 1,012 met the criteria for horizontal concomitant strabismus (642 esotropia and 370 exotropia), while 1,244 non-strabismic children served as controls. All participants underwent standardized cycloplegic refraction, visual acuity assessment, and ocular alignment testing. Group differences were examined using Chi-square tests, and logistic regression was used to identify refractive predictors. Children with esotropia were younger (mean age 8.24 ± 2.89 years) and exhibited a marked hyperopic profile, with 78% having spherical equivalent hyperopia ≥ +2.00 D; clinically significant anisometropia (≥2.50 D) was present in 33.8% of cases. Exotropia occurred at a slightly older age (8.75 ± 2.89 years) and was associated with higher proportions of myopia (53.5%) and astigmatism ≥1.00 D (55.7%). Across the full cohort, myopic refractive error (SE <−0.50 D) was present in 310 children (13.7%), hyperopic refractive error (SE ≥ +2.00 D) in 1,002 (44.4%), astigmatism ≥1.00 D in 555 (24.6%), and anisometropia ≥0.50 D in 1,489 (66.0%). In multivariable analysis, moderate-to-high hyperopia strongly predicted esotropia, whereas myopia and clinically significant astigmatism independently predicted exotropia. These findings show contrasting refractive profiles in Iraqi children with esotropia and exotropia and support the clinical value of early cycloplegic refraction in children with suspected ocular misalignment.